Complete digital workflow for the production of implant‐supported single‐unit monolithic crowns. Issue 11 (8th October 2013) - Joda, Tim; Brägger, Urs
Abstract: Objectives: The aim of this case series was to introduce a complete digital workflow for the production of monolithic implant crowns. Material and methods: Six patients were treated with implant‐supported crowns made of resin nano ceramic (RNC). Starting with an intraoral optical scan (IOS), and following a CAD/CAM process, the monolithic crowns were bonded either to a novel prefabricated titanium abutment base (group A) or to a CAD/CAM‐generated individualized titanium abutment (group B) in premolar or molar sites on a soft tissue level dental implant. Economic analyses included clinical and laboratory steps. An esthetic evaluation was performed to compare the two abutment‐crown combinations. Results: None of the digitally constructed RNC crowns required any clinical adaptation. Overall mean work time calculations revealed obvious differences for group A (65.3 min) compared with group B (86.5 min). Esthetic analysis demonstrated a more favorable outcome for the prefabricated bonding bases. Conclusions: Prefabricated or individualized abutments on monolithic RNC crowns using CAD/CAM technology in a model‐free workflow seem to provide a feasible and streamlined treatment approach for single‐edentulous space rehabilitation in the posterior region. However, RNC as full‐contour material has to be considered experimental, and further large‐scale clinical investigations with long‐term follow‐up observation are necessary.